(untitled) (Indian Journal of Nematology, 2025)
Root-knot nematode, Meloidogyne incognita, is one of the most damaging plant parasitic pathogens in horticultural and agricultural crops. The present study is based on a novel synergistic combination of peptides derived from CED-4 protein demonstrating promising nematicidal activity against M. incognita. In laboratory studies, second-stage juveniles (J2) of M. incognita were directly exposed to peptides 3 and 12 at concentrations of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, and 0.8 mg/ml, respectively for the individual and combined peptides in the ratio of 1:1. It was revealed that 0.6 mg/ml and higher doses were more efficient at limiting the survival of root-knot nematode J2. However, combining peptides in a 1:1 ratio was more effective against M. incognita. Maximum J2 mortality of 89 and 94.4 per cent was observed at 0.7 and 0.8 mg/ml after 24 hrs of exposure, with an LC50 value of 0.38 mg/ml in the combined peptides. Likewise, the in vitro assessment of peptides against egg hatching of M. incognita was also evaluated. A gradual decrease in the rate of egg hatching of M. incognita with an increase in the concentration of peptides was observed. The combined peptides reduced egg hatching to the highest levels of 0.7 mg and 0.8 mg/ml (74.58 and 76.14%), respectively, after seven days of washing of the egg masses in sterile distilled water. The findings indicate root-knot nematode juvenile mortality by different peptide concentrations, whether used alone or in combination of 1:1, and egg hatching was also hindered. Information derived from the current study suggests that the new molecules of peptides derived from the cell death protein 4 (CED-4) of C. elegans can be used for the management of M. incognita and could be a worthy alternative to synthetic nematicides.